INTEGRATING LEARNING MODELS IN BUILDING CRITICAL THINKING SKILLS IN STUDENTS IN ISLAMIC RELIGIOUS EDUCATION LESSONS AT STATE ISLAMIC JUNIOR HIGH SCHOOL 1, SOUTH TANGERANG CITY - Syarif, Fajar; Komarudin, Komarudin (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
The purpose of this study is to explore the application of discovery learning and problem-based learning on students' critical thinking skills in Islamic Religious Education at State Islamic Junior High School 1, South Tangerang City. To achieve this objective, the author used a qualitative research method by analyzing data from interviews, observations, and document analysis related to the implementation of discovery learning and problem-based learning on critical thinking skills in Islamic Education at State Islamic Junior High School 1, South Tangerang City. The results of the study on the implementation of discovery learning and problem-based learning in Islamic Religious Education subjects show that there is an effect of applying discovery learning and problem-based learning methods on students' critical thinking skills. The supporting and inhibiting factors for the implementation of discovery learning and problem-based learning are teacher factors, student factors, and educational environment factors